(untitled) (Razi Medical Journal, 2025)
Antibiotic resistance is a significant public health challenge globally, and Libya is no exception. The misuse and overuse of antibiotics, particularly through self-medication, have contributed to the emergence and spread of resistant bacterial strains. This review explores the current state of antibiotic resistance in Libya, the prevalence and drivers of antibiotic self-medication, and the implications for public health. It also discusses potential strategies to address the issue, including public awareness campaigns, regulatory reforms, and improved healthcare infrastructure.